MAIN ASPECTS OF THE BALANCE SHEET FORMATION: PURPOSE, TASKS AND PROBLEMS - Mikhalyonok, N.O (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The results of financial and economic activity of any enterprise following the results of the reporting period are reflected in various forms of reporting regulated at the legislative level. The balance sheet of the organization is one of the main forms of reporting, which is made up of all business entities - legal entities without exception. This form of reporting is a reflection of the structure and composition of the property of the organization and the sources of such property at the reporting date. One of the most important functions of the balance sheet is its informativeness, as the balance sheet data are the most important analytical tool. The balance sheet enables a wide range of users of accounting (financial) statements to assess and analyze the financial and property status of the enterprise. Based on the results of the balance sheet analysis, appropriate decisions are made depending on the category of users of accounting (financial) statements, and the organization is managed on the basis of analysis and systematization of information on the company's economic activities. To date, the practice of compiling and analyzing the balance sheet reflects that neither the quantitative composition nor the qualitative content of this form of reporting is not a perfect carrier of operational information, on the basis of which it would be possible to make effective administrative decisions, to justify the tactics and strategy of the company's development in the future. Despite the unity of the requirements for the order of reflection of the company's performance in the balance sheet, the specifics of the activities of a separate organization and the features of resource management can significantly distort the actual financial and property status of the business entity.